1998
DOI: 10.1159/000030298
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Needle Ablation of the Prostate: An Alternative Minimally Invasive Therapeutic Concept in the Treatment of Benign Prostate Hyperplasia

Abstract: Alternative minimally invasive methods treating benign prostate hyperplasia (BPH) have become more and more important. Transurethral needle ablation (TUNATM) has been demonstrated to be effective in both canine and the human prostate. The goal of our study was to prove the safety, feasibility and tolerance of this new procedure. In this prospective nonrandomized study, 33 patients underwent TUNATM-treatment. One, 3 and 6 months postoperatively, follow-up examinations were carried out asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, half of these patients also maintained an overall efficacy of more than ‘good’ during 30 months of postoperative follow‐up. Several studies 2 – 8 have reported similar short‐term results whereby TUNA therapy significantly improved IPSS, QOL score and Q max at 3–6 months after the treatment and this therapeutic efficacy persisted for about 12–18 months of follow‐up. However, the authors did not assess in detail how long the significantly decreased level of PV was maintained after the treatment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, half of these patients also maintained an overall efficacy of more than ‘good’ during 30 months of postoperative follow‐up. Several studies 2 – 8 have reported similar short‐term results whereby TUNA therapy significantly improved IPSS, QOL score and Q max at 3–6 months after the treatment and this therapeutic efficacy persisted for about 12–18 months of follow‐up. However, the authors did not assess in detail how long the significantly decreased level of PV was maintained after the treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Anatomical debulking of the adenoma is primarily the most effective and radical therapy for bladder outlet obstruction caused by BPH, whereas functional therapy using α 1 ‐receptor blockade and deactivation of detrusor overactivity for BPH symptoms is an incipiently common and easy, but is not a curative alternative to surgery. The underlying mode of action responsible for the improvement in symptoms after TUNA therapy still remains obscure because several studies have concluded that change in whole prostate volume was minimal as a result of TUNA therapy, even though good clinical outcomes of TUNA have been demonstrated 2–8 . However, postoperative endoscopic observation often reveals that a compressed prostatic urethra can be treated successfully by selective coagulation with TUNA and opened, in spite of minimum change, in the whole prostate volume.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our research into the literature, a total of 7 urodynamic controlled studies with TUNA were identified [22][23][24][25][26]. The followup varied from 6 to 24 months.…”
Section: Urodynamic Studiesmentioning
confidence: 99%
“…The results presented above show that marked improvements in urodynamic parameters can be achieved by TUNA, thus justifying its use for high-risk patients (ASA III-IV). In the course of this literature research, 3 studies were found that investigated the efficacy of TUNA for patients in urinary retention [26,28,29]. In 70% of the patients, normal voiding could be restored.…”
Section: Tuna In Patients In Urinary Retentionmentioning
confidence: 99%